2005
DOI: 10.1143/jjap.44.5759
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of Micro Probe Beam Using MEMS Technology for New Vertical Silicon Probe Card

Abstract: A silicon micro probe beam using a curled cantilever was designed and fabricated using microelectromechanical systems (MEMS) technology, such as porous silicon micromachining, reactive ion etching (RIE) and Au electroplating. The stress analysis of a micromachined micro probe beam was performed using finite-element ANSYS software. As a result, the basic structure was a multilayer composed of Au/Ni–Cr/Si3N4/n-epi layers. The width and length of the micro probe beam were 40 µm and 600 µm, respectively. Annealing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2006
2006
2009
2009

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…The techniques for manufacturing cantilever beams have been widely applied in atomic force microscopy (Gupta et al 2003), micro-resonators (Tellier and Leblois 2006), chemical reaction detectors (Abedinov et al 2004), environmental sensors (Lee and Lee 2003;Lee et al 2006a, b), micro probe cards (Kim et al 2005) and bio-molecular manipulation devices (Tuomas et al 2008). It has been shown that the coating of a silicon (Si) micro-cantilever structure with a thin layer of an appropriate material such as silicon nitride (SiN x ) induces a thermal coefficient mismatch which causes the cantilever beam to deflect in the upward direction when subjected to thermal loading.…”
Section: Introductionmentioning
confidence: 99%
“…The techniques for manufacturing cantilever beams have been widely applied in atomic force microscopy (Gupta et al 2003), micro-resonators (Tellier and Leblois 2006), chemical reaction detectors (Abedinov et al 2004), environmental sensors (Lee and Lee 2003;Lee et al 2006a, b), micro probe cards (Kim et al 2005) and bio-molecular manipulation devices (Tuomas et al 2008). It has been shown that the coating of a silicon (Si) micro-cantilever structure with a thin layer of an appropriate material such as silicon nitride (SiN x ) induces a thermal coefficient mismatch which causes the cantilever beam to deflect in the upward direction when subjected to thermal loading.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] Among the devices, RF MEMS switches are promising devices for wireless applications because of various advantages such as their low insertion loss, high isolation, negligible power consumption and wide frequency band coverage, as they have demonstrated superior RF characteristics compared to the conventional solid-state switches. 4) The major concerns for the commercialization of the RF MEMS switches are related to the reliability of the metal contacts.…”
Section: Introductionmentioning
confidence: 99%
“…The electrical metal contacts have been more important issues in microelectromechanical systems (MEMS) such as radio frequency (RF) switches, mechanical relays, and wafer probe cards for developing the performance and reliability of the miniaturized devices. [1][2][3][4] Among the devices, RF MEMS switches are promising devices for wireless applications because of various advantages such as their low insertion loss, high isolation, negligible power consumption and wide frequency band coverage, as they have demonstrated superior RF characteristics compared to the conventional solid-state switches. 4) The major concerns for the commercialization of the RF MEMS switches are related to the reliability of the metal contacts.…”
Section: Introductionmentioning
confidence: 99%